Effects of Music Therapy on Physiological Indicators and Subjective Comfort in Patients Undergoing Large Medical Imaging Examinations: A Systematic Review and Meta‐Analysis - Zefang Li; Tiexiong Wu; Haina Fu (Journal of Medical Imaging and Radiation Oncology, 2026)
ABSTRACT Objective To systematically evaluate the effects of music therapy on physiological indicators and psychological states in patients undergoing large medical imaging examinations, providing evidence‐based support for clinical auxiliary interventions. Methods A comprehensive literature search was conducted across English and Chinese databases, including PubMed, Embase, Cochrane Library, Web of Science, CNKI, Wanfang Database, and VIP Database, from inception to May 2026. RCTs investigating music therapy interventions in patients undergoing medical imaging examinations were collected. Two independent reviewers performed literature screening, data extraction, and quality assessment. A meta‐analysis was conducted on outcome indicators including heart rate, anxiety scores, depression scores, and examination cooperation rate. Heterogeneity among studies was evaluated using the I 2 statistic. Results A total of 9 RCTs were included. The meta‐analysis results demonstrated that music therapy significantly reduced patients' heart rates, with a pooled mean difference (MD) of −2.14 (95% CI: −2.21, −2.08; p < 0.05). It also significantly alleviated anxiety levels, with a pooled SMD of −1.43 (95% CI: −1.49, −1.38; p < 0.05). The analysis of depression scores indicated no statistically significant difference between the two groups (SMD = 0.11, 95% CI: −0.62, 0.84; p = 0.77). The analysis of examination cooperation rates showed that music therapy improved the examination cooperation rate, with a pooled risk ratio (RR) of 1.34 (95% CI: 1.28, 1.40; p < 0.05). High heterogeneity was observed in certain outcome indicators. Conclusion Music therapy can, to a certain extent, improve the physiological and psychological states of patients undergoing medical imaging examinations, as manifested by reduced heart rates, alleviated anxiety, and an increased examination cooperation rate. However, its efficacy in improving depressive states remains unclear. Given the high heterogeneity in some analytical results, further large‐sample, high‐quality RCTs are required for verification.